Extremism and Flattery and How to Face Them | التطرف والمداهنة وكيفية التصدي لهما - Najm Abd Rahman (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
Today moderation of Islam faces severe challenges. Through this paper presented diagnosis of this social disease and it cure, by suggesting the correct understanding of two terms; extremism, and flattery, so it does not cause negative effects for individuals and groups. The important goals of this research be alert contemporary muslim generation from extremism, fanaticism and hypocrisy.